2016
DOI: 10.1017/s0021859616000903
|View full text |Cite
|
Sign up to set email alerts
|

Genotypic and environmental variability of yield from seven different crops in Croatian official variety trials and comparison with on-farm trends

Abstract: SUMMARYAssessment of the value for cultivation and use (VCU) of a new cultivar, essential for its official registration, is done through a series of trials carried out over a 2–3-year period and across many locations. In a set of multi-environment VCU trials, evaluation of new genotypes can be a laborious task due to the presence of genotype by environment interactions, which can hide their true genetic value. In an attempt to reveal the true genetic value of new cultivars, a good starting point is investigati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 16 publications
1
2
1
Order By: Relevance
“…Severe weather, primarily heat, had a stronger effect on earlier-maturity groups, as indicated in our results across five maturity groups. Similar results were presented in comparable official plant variety trials (VCU) in Croatia, where a greater component of variance for year was noted in earlier maize maturity groups [30]. Generally, grain yield declined during the twenty years of our experiment in all FAO groups; however, the decrease was the smallest in FAO 600.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Severe weather, primarily heat, had a stronger effect on earlier-maturity groups, as indicated in our results across five maturity groups. Similar results were presented in comparable official plant variety trials (VCU) in Croatia, where a greater component of variance for year was noted in earlier maize maturity groups [30]. Generally, grain yield declined during the twenty years of our experiment in all FAO groups; however, the decrease was the smallest in FAO 600.…”
Section: Discussionsupporting
confidence: 88%
“…According to the results of the present study, planting predominantly early maize hybrids in the European Corn Belt does not seem to be an optimum option in the future, since these hybrids are more sensitive to omnipresent heat stress than late hybrids. However, it was previously demonstrated in VCU trials in Croatia that the location × year interaction significantly contributed to the total variance in maize grain yield [30], which could not be captured in the present study. Thus, our next step will be to analyze robust multilocational official long-term VCU data across several maize maturity groups to disentangle the effects of climate change from those of genetic progress and of all other agronomic factors changed over time.…”
Section: Discussioncontrasting
confidence: 84%
“…Similarly, in the study of MULEMA et al (2008), who analyzed tuber yield of 12 potato genotypes across 12 environments, the E, G, and G×E sources of variation explained 54, 11 and 25% of the total sum of squares, respectively. Relatively low contribution of genetic variance to the total variance was also reported for yield of other crop species (FRIESEN et al, 2016;ZORIĆ et al, 2017). On the other hand, FLIS et al, (2014), in a study analyzing tuber yield of potato genotypes from three series of regional trials in Europe (Poland, Hungary and Spain), reported a higher contribution of location (58%) to the total sum of squares.…”
Section: Analysis Of Variancementioning
confidence: 87%
“…The genotypic main effect plus GE interaction (GGE biplot) analysis used by agricultural researchers, in particular, plant breeders had enhanced dramatically for analyzing multi-environment trial (MET) data (Yan et al 2007). In the last step of a breeding program finishing by cultivar release, which had a large numbers of advanced breeding lines, it is possible to characterize each genotype in terms of its stability in countered with diverse environmental conditions (Cooper and DeLacy, 1994;Xu et al, 2017;Zoric et al, 2017 andHassani et al, 2018). A review of the recent literatures represent that attempts have been made to separate the effects of GEI on wheat grain yield traits, and other crops using sophisticated multivariate statistical methods (Yan, 2016;Hassani et al, 2018;Yan and Frégeau-Reid, 2018).…”
Section: Introductionmentioning
confidence: 99%